Short-term exposure to particulate matter triggers a selective alteration of plasma extracellular vesicle-packaged miRNAs in a mouse model of multiple sclerosis - Martino Bonato; Valentina Cerrato; Laura Dioni; Francesca Montarolo; Roberta Parolisi; Antonio Bertolotto; Antonio Bertolotto; Valentina Bollati; Luca Ferrari; Enrica Boda (Frontiers in Immunology)
Epidemiological studies have highlighted the existence of population groups exhibiting a higher sensitivity to the impact of environmental factors, such as exposure to air pollution. In these regards, people with Multiple Sclerosis (MS) or predisposed to develop MS - an autoimmune disorder of the Central Nervous System (CNS) - appear as a more vulnerable cohort to the effects of particulate matter (PM) exposure. Here, we aimed at disclosing the biological substrate of such higher vulnerability, and specifically at understanding whether individuals primed to develop autoimmunity (as it occurs in MS and in the experimental autoimmune encephalomyelitis - EAE - animal model of MS) respond differently to PM compared to healthy subjects. To this purpose, we characterized plasmatic extracellular vesicles (EVs) and their microRNA (miRNA) cargo in healthy and presymptomatic EAE mice early after exposure to PM10, compared to unexposed healthy and EAE mice. Results showed that the response of EAE mice to PM10 did not differ in terms of EV number or source, compared to that of healthy mice. Yet, remarkable differences existed in the identity of deregulated EV-associated miRNAs, which, in EAE mice, were predicted to target several MS-relevant biological processes and nervous system-, immune- and inflammation-related pathways, possibly contributing to disease worsening.